Elusive pirates, pervasive smugglers : violence and clandestine trade in the Greater China Seas - Antony, Robert J. (Hong Kong University Press, 2010)
This volume describes and critically analyzes piracy and smuggling in the Greater China Seas region from the 16th century to the present. It takes a radical departure from the standard terra-centred histories by placing the seas at the centre rather than at the margins of our inquiries.